Effect of Deficit Irrigation on Agronomic and Physiological Performance of Pomegranate (Punica granatum L.) - Rossana Porras-Jorge; José Mariano Aguilar; Carlos Baixauli; Julián Bartual; Bernardo Pascual; Nuria Pascual-Seva (Plants)
Abstract: Agriculture accounts for over 70% of global freshwater consumption, with increasing competition for water resources due to climate change and rising urban and industrial demands. This study analyzes the effect of deficit irrigation (DI) on the agronomic and physiological performance of pomegranate (Punica granatum L.) in a Mediterranean climate. Deficit irrigation strategies, including sustained deficit irrigation (SDI) and regulated deficit irrigation (RDI), were evaluated against a control with full irrigation. The research was conducted over two growing seasons (2022–2023) at the Cajamar Experimental Centre in Paiporta, Valencia, Spain. RDI strategies achieved approximately 10% water savings without compromising marketable yield or fruit weight, while SDI resulted in significant water savings (~50%) but with a notable reduction in marketable yield, particularly in hot and dry conditions. SDI also reduced tree growth in height and trunk diameter compared to RDI and control strategies. The study concludes that RDI is a viable irrigation strategy for pomegranate cultivation under water-limited conditions, whereas SDI should be reserved for situations of severe water scarcity.